Documents in the Criminal Code of Ukraine: Content and Their Relationship - M. I. Fialka (Bulletin of Kharkiv National University of Internal Affairs)
The subject matter of the scientific research carried out within the scientific article are documents as features of corpus delicti provided in the criminal legislation of Ukraine. The purpose of this article is to study the problem of the existence of the document, its varieties and their relationship in the structure of the Criminal Code of Ukraine. Achieving this purpose within the study became possible due to the implementation of the relevant tasks, namely: to determine the list of criminal and legal norms, which provide the presence of a document in the form of certain features of corpus delicti; to establish the main content and essence of each type of the document; to establish the relationship of different types of documents in the structure of the Criminal Code of Ukraine.